2008
DOI: 10.1523/jneurosci.1660-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interaural Time Difference Processing in the Mammalian Medial Superior Olive: The Role of Glycinergic Inhibition

Abstract: The dominant cue for localization of low-frequency sounds are microsecond differences in the time-of-arrival of sounds at the two ears [interaural time difference (ITD)]. In mammals, ITD sensitivity is established in the medial superior olive (MSO) by coincidence detection of excitatory inputs from both ears. Hence the relative delay of the binaural inputs is crucial for adjusting ITD sensitivity in MSO cells. How these delays are constructed is, however, still unknown. Specifically, the question of whether in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
274
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(303 citation statements)
references
References 62 publications
27
274
2
Order By: Relevance
“…In the mammalian MSO, inhibition is crucial for the proper tuning of ITD sensitivity (Brand et al, 2002;Pecka et al, 2008) and it has been suggested that precisely timed inhibitory drive sets the time window for neuronal coincidence detection (Pecka et al, 2008). Thus, if STD supports coincidence detection, and if the inhibitory inputs to the MSO are temporally aligned to the excitation, both the excitation and inhibition should have similar STP profiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the mammalian MSO, inhibition is crucial for the proper tuning of ITD sensitivity (Brand et al, 2002;Pecka et al, 2008) and it has been suggested that precisely timed inhibitory drive sets the time window for neuronal coincidence detection (Pecka et al, 2008). Thus, if STD supports coincidence detection, and if the inhibitory inputs to the MSO are temporally aligned to the excitation, both the excitation and inhibition should have similar STP profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies show that MSO neurons can fire at very high rates, locking precisely to the phase of pure tones (Brand et al, 2002). Thus, given this circuit relies on temporally precise inhibition and excitation (Brand et al, 2002;Pecka et al, 2008), we expect these inputs to behave similarly during high-frequency stimulation in vitro. Therefore, we hypothesize that the recruitment of a set of strong and fast synaptic inputs establishes the presynaptic basis for the exquisite coincidence detection in MSO neurons.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We focused on the sustained response because responses of IC neurons to electric pulse trains are often limited to brief burst of spikes at stimulus onset at high stimulation rates (Smith and Delgutte 2007;Hancock et al 2012). These electric responses contrast with responses to acoustic pure tones which show sustained response throughout stimulus durations in a majority of IC and MSO neurons (Pecka et al 2008).…”
Section: Simulations and Data Analysismentioning
confidence: 99%
“…Juxtacellular and intracellular whole-cell in vivo data have only recently been reported (Franken et al, 2013;van der Heijden et al, 2013). In the absence of a large corpus of intracellular or even extracellular data, debates continue regarding the distribution of interaural delays (McAlpine and Grothe, 2003;Joris and Yin, 2007) and the kinetics and timing of inhibition (Brand et al, 2002;Grothe, 2003;Zhou et al, 2005;Pecka et al, 2008; and excitation (Jercog et al, 2010;. Systematic theory-based analyses of the neurophonic, a more accessible in vivo data source, may offer new perspectives on these puzzles and provide a bridge between in vivo data obtained in larger species (cat, dog, monkey) and small-headed rodents (gerbil, guinea pig, chinchilla).…”
Section: Signatures Of Mso Biophysics In the Neurophonicmentioning
confidence: 99%